Washback effects of Google Meet automatic caption feature in assessing students’ pronunciation - Ramadhika, Boris; Karma, Carolus Prima Ferri; Yosintha, Rolisda (Universitas Islam Sultan Agung, 2023)
The utilisation of technology in assessing speaking tests is not a novel concept. Conducting an analysis of the washback effect should be done following the implementation of the assessment. This research study aimed at finding the washback effects of the use of the Google Meet automatic caption feature in assessing students’ pronunciation skill. A mixed-method was employed with the embedded case study as the research design. The instrument was a survey questionnaire designed with a four-point Likert scale. It was distributed to 63 students in English subject from the first semester of Management study program in Universitas Tidar, Magelang which were selected using the purposive sampling. A descriptive statistics analysis was used to analyze the results of the questionnaire. To strengthen the data, a semi-structured interview was conducted to gain more accurate descriptive data. It was found that there are three pedagogical dimensions of washback effects: students’ attitudes, motivation, and pronunciation awareness. Based on these results, further research on the feature’s accurateness in captioning is highly suggested.